History and Basic Principles of Photodynamic Therapy Use in Ophthalmology - Abdul Karim Ansyori (Sriwijaya Journal of Ophthalmology, 2021)
Photodynamic therapy (PDT) is a therapy that uses drugs, called photosensitizers or photosensitizing agents, and a specific type of light. When photosensitizers are exposed to certain wavelengths of light, they produce oxygen that kills nearby cells. PDT is achieved by a photodynamic reaction induced by the excitation of a photosensitizer exposed to light. In the field of ophthalmology, PDT was approved for the first time about ten years ago for cases of age-related macular degeneration (AMD). Neovascular age-related macular degeneration (AMD) is a vision-threatening disease characterized by pathological macular neovascularization. After that, PDT was approved for use in choroidal neovascularization (CNV) cases in pathological myopia.3 This literature review aims to describe the history of PDT use and the basic principles of photodynamic therapy in ophthalmology.